Effectiveness of Education Module Implementation on Increasing Islamic Financial Literacy and Halal Literacy of MSMEs Perpetrators - Nur Wahyuny, Ikka; Murtini, Wiedy; Hakim, Lukman (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2018)
This research was conducted to measure the impact of the implementation of Islamic Financial Literacy Education Module and Halal Product for Micro, Small and Medium Enterprises (MSMEs). The population in this study is the perpetrators of SMEs that run their business in the region of Yogyakarta Special Region. The sampling technique used is purposive sampling so that the sample used is 60 with the division of 30 experimental group and 30 people as the control group. Development of media using ADDIE model. Educational module has been through the phase of analysis, design, development, and implementation of MSMEs. At the evaluation stage, measurements are made to the perpetrators of SMEs with paired t test. The results of effectiveness test show the use of Islamic Financial Literacy Education Module and Halal Product can increase Islamic financial literacy and halal literacy of MSMEs perpetrators. Increased Islamic financial literacy and halal literacy can be seen from the average score before and after the use of Islamic financial literacy learning module and halal literacy. The conclusion of this research is a module with an important syariah theme done to provide ease in the transfer of knowledge of Islamic financial management and halal literacy for MSMEs.